Multiscale polyethylene fiber – bacterial nanocellulose composites through combined laser fusion and bacterial in situ synthesis - Schlicht, Samuel; Wesinger, Mara; Kaufmann, Anke; Fischer, Dagmar; Drummer, Dietmar (International Polymer Processing, 2025)
Ultra-high molecular weight polyethylene (UHMW-PE) fibers and bacterial nanocellulose (BNC) display exceptional mechanical properties alongside the outstanding tribological properties of UHMW-PE while showing unrestricted biocompatibility. For combining the intrinsic advantages of both materials, the present work demonstrates an approach that integrates the slurry-based laser fusion of PE-polyvinylpyrrolidone (PE-PVP) composites and the subsequent bacterial biosynthesis of nanocellulose. PE-PVP composites exhibiting a fraction of 10 % of UHMW-PE fibers were additively manufactured through the locally selective laser-based layer-wise evaporation and subsequent sintering of aqueous suspensions, yielding fiber composites with a water-soluble matrix. The in situ synthesis of bacterial nanocellulose exploits the gelling and dissolving of high-molecular PVP in aqueous media. By allowing for the infiltration of printed PE-PVP composites with nanocellulose-producing Komagataeibacter xylinus, a multiscale composite of polyethylene fibers and bacterial nanocellulose was obtained, corroborating the infiltration of micrometer-scale PE fibers with nanoscale cellulose fibers. Release experiments using methylene blue confirmed the potentials of PE-BNC composites for drug delivery applications, showing first order sigmoidal release kinetics.